Predicting social media use among public relations practitioners applying technology acceptance model (TAM) - El-Kasim, Mukhtar (Kuliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The emergence and diffusion of the social media have transformed the way public relations is practiced across the globe. Social media provides more opportunities of engagement between organizations and the public. Studies establish that social media has great influence and impact in shaping relationships that exist between organizations and their strategic publics. However, most of the empirical findings on social media and relationship building are carried out in advanced nations such as the US, the UK, and Canada. Still, little is known about the influence of the social media on public relations practice in developing nations. Moreover, most of the studies conducted on the relevance and influence of the social media in PR practice in those developed countries were not guided by a theory. Hence, the utmost need to investigate the relevance and influence of the social media from developing countries angle. This study therefore, investigates the social media use among the Nigerian PR Practitioners. The study utilized Technology Acceptance Model as the theoretical framework. TAM posits that a potential user of a specific Information System (IS) may use it because of its perceived usefulness (PU) and perceived ease of use (PEU), moreover, these two determinants influence his/her behavioural intention (BI) for actual use. Hence, this study proposes a model which explains how practitioners use the social media for enhancing mutual relationships by providing two constructs which explain the actual use of social media among practitioners, namely, perceived mutual relationships, measured from three dimensions (trust, commitment and satisfaction) and perceived interactivity, measured from another three dimensions (active control, two-way communication and synchronization). Data were collected from 513 PR practitioners through self-administered questionnaire nation-wide. Structural Equation Modelling (SEM) was employed for testing the study's hypotheses. The study's hypotheses were broadly divided into two: at the first level were hypotheses that tested TAM as the theoretical guide of this study, and at the second level, hypotheses that tested our constructs which explained how practitioners actually use the social media for enhancing mutual relationships with their publics. From the TAM level, the findings indicate significant relationships between the variables: PEU to PU (β=.88, p=.000); PU to BI (β=.28, p=.002); PEU to BI (β=.48, p=.000); PU to SM (β=.44, p=.000) and BI to SM (β=.55, p=.000). The findings of the hypotheses that tested the use of the social media for enhancing mutual relationships at the second level, suggest statistically positive and significant relationships between social media use and enhancing mutual relationships: SM to TR (β=.93, p=.000); SM to CM (β=.92, p=.000); SM to ST (β=.91, p=.000); SM to AC (β=.54, p=.000); SM to TC (β=.87, p=.000); and SM to SY (β=.82, p=.000). The findings prove the proposed model of this study which explains the relevance and influence of the social media for enhancing mutual relationships between organizations and the publics. The theoretical and managerial implications of this study are also presented and discussed.